1991
DOI: 10.1079/bjn19910010
|View full text |Cite
|
Sign up to set email alerts
|

Apparent zinc absorption by rats from foods labelled intrinsically and extrinsically with 67Zn

Abstract: A variety of foods (peas (Pisum sativum), chicken meat, eggs, goat's milk, human milk) enriched with the stable isotope 67Zn were prepared by means of intrinsic- and extrinsic-labelling procedures. They were fed to rats and apparent absorption of 67Zn determined from faecal excretion measurements using thermal ionization mass spectrometry. There were significant differences in the absorption of the extrinsic and intrinsic label which differed in magnitude between the foods tested. The extrinsic 67Zn was less w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 13 publications
0
21
0
Order By: Relevance
“…Published studies comparing absorption of intrinsic and extrinsic Zn isotope tracers have provided inconclusive results. Six reports of such studies in rats demonstrated either no significant difference or that the extrinsic tracer was absorbed to a greater or lesser extent (14)(15)(16)(17)(18)(19). Of 6 studies in humans, 4 found no significant difference, whereas 2 studies indicated that the extrinsic label was absorbed at a lower level (20)(21)(22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 98%
“…Published studies comparing absorption of intrinsic and extrinsic Zn isotope tracers have provided inconclusive results. Six reports of such studies in rats demonstrated either no significant difference or that the extrinsic tracer was absorbed to a greater or lesser extent (14)(15)(16)(17)(18)(19). Of 6 studies in humans, 4 found no significant difference, whereas 2 studies indicated that the extrinsic label was absorbed at a lower level (20)(21)(22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 98%
“…Many studies have been performed to validate the extrinsic labelling approach, in particular for Zn, with contradictory results. Even if it is still not certain that the isotope behaves in exactly the same way as the native Cu or Zn bound in the food matrix (Fairweather-Tait et al 1991;Fox et al 1994;Boza et al 1995), it is accepted that extrinsic labels may be used as an approximate guide when assessing the bioavailability of Cu and Zn from different regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Zinc isotope ratios 64:67, 66:68 and 67:68 measured by RPC-ICP-MS were in good agreement with those determined by FIA and DNIR. The intrinsically labelled chicken meat was prepared by Fairweather-Tait et al [12] for an experiment to monitor apparent 67Zn absorption in rats. They expressed the degree of 67Zn enrichment achieved by intrinsic labelling of the chicken meat using the 64:67 ratio measured as 3.05, and the naturally occurring 64:67 ratio as 11.85.…”
Section: ( I ) Zn Speciation In An In Vitro Enzyme Digest Of Chicken mentioning
confidence: 99%